SAMHD1 restricts HIV-1 replication and regulates interferon production in mouse myeloid cells. - Ruonan Zhang; Nicolin Bloch; Laura A Nguyen; Baek Kim; Nathaniel R Landau (PLoS ONE)
SAMHD1 restricts the replication of HIV-1 and other retroviruses in human myeloid and resting CD4(+) T cells and that is counteracted in SIV and HIV-2 by the Vpx accessory protein. The protein is a phosphohydrolase that lowers the concentration of deoxynucleoside triphosphates (dNTP), blocking reverse transcription of the viral RNA genome. Polymorphisms in the gene encoding SAMHD1 are associated with Aicardi-Goutières Syndrome, a neurological disorder characterized by increased type-I interferon production. SAMHD1 is conserved in mammals but its role in restricting virus replication and controlling interferon production in non-primate species is not well understood. We show that SAMHD1 is catalytically active and expressed at high levels in mouse spleen, lymph nodes, thymus and lung. siRNA knock-down of SAMHD1 in bone marrow-derived macrophages increased their susceptibility to HIV-1 infection. shRNA knock-down of SAMHD1 in the murine monocytic cell-line RAW264.7 increased its susceptibility to HIV-1 and murine leukemia virus and increased the levels of the dNTP pool. In addition, SAMHD1 knock-down in RAW264.7 cells induced the production of type-I interferon and several interferon-stimulated genes, modeling the situation in Aicardi-Goutières Syndrome. Our findings suggest that the role of SAMHD1 in restricting viruses is conserved in the mouse. The RAW264.7 cell-line serves as a useful tool to study the antiviral and innate immune response functions of SAMHD1.